2011
DOI: 10.1094/cchem-01-11-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultivar and Processing Condition on Physicochemical Properties and Starch Fractions in Parboiled Rice

Abstract: Cereal Chem. 88(4):414-420Starch can be classified into rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) according to its resistance to amylolytic enzymes. This study investigated the effects of cultivar and feedstock under varying parboiling conditions on the physicochemical properties and starch fractions of parboiled rice. Rice (rough or brown) was soaked, steamed under pressure, dried immediately or stored at room temperature for 24 hr prior to drying, and then tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The specific temperatures to form amylose-lipid complexes are dependent on lipid characteristics (Tufvesson et al 2003). The enthalpy values of amylose-lipid complex were similar to those reported by Newton et al (2011). The lack of significant differences in amylose-lipid complex melting between germination durations for both cultivars agrees with the previous study (Han et al 2016) and suggests that germination did not sufficiently alter amylose molecular size to change its interaction with lipids.…”
Section: Resultssupporting
confidence: 87%
“…The specific temperatures to form amylose-lipid complexes are dependent on lipid characteristics (Tufvesson et al 2003). The enthalpy values of amylose-lipid complex were similar to those reported by Newton et al (2011). The lack of significant differences in amylose-lipid complex melting between germination durations for both cultivars agrees with the previous study (Han et al 2016) and suggests that germination did not sufficiently alter amylose molecular size to change its interaction with lipids.…”
Section: Resultssupporting
confidence: 87%
“…These results suggest that a greater proportion of the starch granules in NERICA7 remains ungelatinized due to an unknown resistance even at severe steaming conditions, while the starch granules in the other varieties are very sensitive to heat and most get gelatinized at moderate steaming conditions. Some authors have reported on the decrease in the viscosity properties of rice flour due to parboiling (Himmelsbach et al., ; Newton et al., ; Soponronnarit, Nathakaranakule, Jirajindalert, & Taechapaorij, ). The decrease in viscosity parameters with increasing steaming time and as a function of rice varieties is in accord with studies by Patindol et al.…”
Section: Resultsmentioning
confidence: 99%
“…Physical changes include increased head rice yield (Buggenhout et al., ), grain translucency, and decreased chalkiness due to starch pregelatinization (Bhattacharya, , ; Delcour & Hoseney, ; Lamberts, Gormand, Deryck, & Delcour, ; Patindol, Newton, & Wang, ), increased grain hardness, and reduced grain breakage due to swelling of the starchy endosperm during gelatinization, which heals the pre‐existing defects (Ndindeng et al., ; Newton, Wang, & Mauromoustakos, ). Chemical changes include lower glycemic index, high‐resistant starch content, and high contents of B vitamins (Jenkins, Wolever, & Jenkins, ; Manful, Grimm, Gayin, & Coker, ; Newton et al., ; Odenigbo, Ndindeng, Nwankpa, Woin, & Ngadi, ; Zohoun et al., ). In addition, parboiling leads to development of some unique aromatic and textural characteristics that are appealing to certain groups of consumers (Demont et al., ; Heinemann, Behrens, & Lanfer‐Marquez, ; Prom‐U‐Thai, Rerkasem, Cakmak, & Huang, ).…”
Section: Introductionmentioning
confidence: 99%
“…A strong negative correlation existed between sample protein content and the size of parboiled brokens (Table 2). While some researchers (Padua & Juliano, 1974) reported a decrease in the protein content of parboiled rice compared to nonparboiled rice, others reported an increase (Dooyum, Woo, Hong, & Ha, 2016;Newton, Wang, & Mauromoustakos, 2011;Sareepuang, Siriamornpun, Wiset, & Meeso, 2008). Some studies also reported a nonsignificant difference between the protein content of parboiled cereal grains such as einkorn wheat (Hidalgo, Brandolini, & Gazza, 2008).…”
Section: Protein Content and Yield Of Rice Samplesmentioning
confidence: 99%